Big data in political communication: implications for group privacy. (20th November 2019) - Mavriki, Paola; Karyda, Maria
A growing body of academic literature explores privacy implications stemming from the adoption of big data analytics technologies in the area of political marketing and communication. While academic and public discourse on privacy focuses on the individual level, this paper explores a scarcely studied issue: group privacy. We elaborate on the importance and role of group privacy showing that even when the members of a group have their data protected, there are still privacy risks concerning the group and we identify and analyse threats to group privacy stemming from the exploitation of big data for political purposes. This paper argues that the use of big data analysis technologies in a political context can have severe implications for group privacy, including (political) targeting of particular groups and biased decision making based on group behaviour. We also show that threats to group privacy may have long term implications for society, especially with regard to the impact of populist movements.